Human capital development and income inequality in Indonesia: Evidence from a nonlinear autoregressive distributed lag (NARDL) analysis - Goh Lim Thye; Siong Hook Law; Irwan Trinugroho (Cogent Economics & Finance, 2022)
Indonesia ranks sixth globally in terms of wealth distribution inequality. Changes in human capital development may affect labor force efficiency and productivity as well as wages and income inequality levels. This study applies a nonlinear autoregressive distributed lag (NARDL) model to data from 1970 to 2019 to investigate the asymmetric impact of human capital development on income inequality in Indonesia. Our results provide significant evidence of the long-run asymmetric effects of human capital development on income inequality. More specifically, income inequality responded more significantly to increase in human capital development than to reduction. Hence, policymakers should establish inclusive lifelong learning systems that concentrate on skill enhancement, such as re-training and re-skilling, and technical and vocational training (TVET) systems to enhance a country's human capital development.
Keywords: D33; D63; J24; 330; asymmetric cointegration; Human capital development; income inequality; Indonesia